Abdijamil Nurpeisov’ s “Last Duty” Dilogy in Mythological Aspect - Enkar T. Kakilbaeva (Polylinguality and Transcultural Practices, 2020)
We made an attempt to consider the poetics of the dilogy by Abdijamil Nurpeisov Last Duty in a mythological aspect, to determine the functions of mythologemes that allow one or another plot situation to be interpreted using parallels from mythology. The subject of research is the multifunctionality of myth, its semantics and structure-forming function. The main attention is paid to the interpretation of mythologemes and the meaning of the actions of the protagonist, whom we consider as a mythological hero. The methodology of the article is based on a multidimensional approach, which involves the use of a comparative historical method that allows us to consider the similarities and differences of plot situations in the text on the basis of direct contacts, historical and genetic - to identify sources of myths and structural-semantic - in order to explore the features of myths in the artistic structure of the novels.